THE ROLE OF T2W PULSE SEQUENCE AND DIFFUSION WITH ITS NUMERICAL ADC MAP IN PROSTATE CANCER DIAGNOSIS - Kostova, Masha; Stojovska Jovanovska, Elizabeta; Dodevski, Ace; Veljanovski, Dimitar; Dejanova Panev, Sandra; Prgova Veljanova, Biljana (Macedonian Association of Anatomists and Morphologists, 2023)
In patients with increased PSA (prostate-specific antigen), the next diagnostics tool is transrectal ultrasound-guided biopsy-TRUS. Multiparametric magnetic resonance imaging (mp MRI) as non invasive diagnostic tool is used as a triage test to avoid biopsy, as well as to improve the diagnostics. In our study we want to prove the clinical meaning of T2W pulse sequence and diffusion as a part of mp MRI in prostate malignant lesions detection and their distinction from the benign lesions. This cohort prospective study included 100 patients with increased levels of PSA from 4 ng/ml to 76 ng/ml. The MRI equipment used was Siemens Essenza1,5T with body coil. The results from the T2W pulse sequence and diffusion are correlated with the values of diffusion and ADC map, in which the suspected zones are marked on a template. Patients undergo biopsy depending on the PIRADS (prostate-imaging and reporting data system) classification. The MRI results and the pathohistological findings are then compared. Clinically significant cancer is considered to be a cancer with a Gleason score 6, diameter > 6mm. The values of diffusion with its numerical ADC map are considerably lower for malignant nodules compared to benign ones. Hyposignal of T2W pulse sequence is characterized with score 2 and 3 in benign changes, and 4 and 5 in malignant changes using the PI RADS score system for differentiation. T2W pulse sequence combined with diffusion is a powerful tool for non-invasive differentiation of benign prostatic hyperplastic nodule and prostatitis from a malignant nodule.
Keywords: prostate carcinoma; multiparametric MRI; T2Wpulse sequence; diffusion with ADC